Konsep adab menuntut ilmu dalam Al-Qur’an dan relevansinya bagi mahasiswa baru - Chamidah, Himma Iliyatul (Maliki Interdisciplinary Journal, 2026)
The etiquette of seeking knowledge is a fundamental value in the Islamic educational tradition, which places ethics, morality, and spirituality as the primary foundation before one enters the process of seeking knowledge. The Qur’an provides a comprehensive ethical framework for how a student should behave, from organizing intentions, humility, and respect for teachers to sincerity, discipline, and critical thinking skills. This article aims to examine the concept of etiquette in seeking knowledge as stated in the Qur’an and analyze its relevance for new students adapting to the academic environment of higher education. Using a thematic analysis approach to Qur’anic verses and referring to the views of scholars, this study finds that etiquette is not merely a moral code, but a practical guideline that can improve students’ intellectual quality and character. The results of the study indicate that the application of etiquette values ​​has a positive impact on students’ academic integrity, learning ethics, time management, social interaction skills, and spiritual maturity. Etiquette has also proven relevant in facing the challenges of the digital era, particularly related to information ethics and critical literacy. Thus, the etiquette of seeking knowledge has a significant contribution in shaping new students into knowledgeable, moral, and responsible individuals, while simultaneously strengthening the role of higher education as a space for character and intellectual development.